2018
DOI: 10.1088/1752-7163/aaa499
|View full text |Cite
|
Sign up to set email alerts
|

The potential role of exhaled breath analysis in the diagnostic process of pneumonia—a systematic review

Abstract: Diagnostic strategies currently used for pneumonia are time-consuming, lack accuracy and suffer from large inter-observer variability. Exhaled breath contains thousands of volatile organic compounds (VOCs), which include products of host and pathogen metabolism. In this systematic review we investigated the use of so-called 'breathomics' for diagnosing pneumonia. A Medline search yielded 18 manuscripts reporting on animal and human studies using organic and inorganic molecules in exhaled breath, that all could… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(39 citation statements)
references
References 86 publications
0
39
0
Order By: Relevance
“…Studies of animal and human pulmonary diseases have identified potential biomarkers from analyses of VOC profiles in exhaled breath which may be used to determine the cause of specific diseases and improve the accuracy of disease diagnostic processes for pneumonia and other respiratory diseases [48]. A summary of metabolomic data collected from several studies on pneumonia showed the same consistent VOCs with changes in concentrations of healthy vs. diseased patients based on VOC profiles based on breathomics.…”
Section: Biomarker Metabolite Electronic-nose Signaturesmentioning
confidence: 99%
“…Studies of animal and human pulmonary diseases have identified potential biomarkers from analyses of VOC profiles in exhaled breath which may be used to determine the cause of specific diseases and improve the accuracy of disease diagnostic processes for pneumonia and other respiratory diseases [48]. A summary of metabolomic data collected from several studies on pneumonia showed the same consistent VOCs with changes in concentrations of healthy vs. diseased patients based on VOC profiles based on breathomics.…”
Section: Biomarker Metabolite Electronic-nose Signaturesmentioning
confidence: 99%
“…Another use of mass spectrometry is in the characterization of volatile organic compounds (VOCs)so-called "breathomics," which has been hailed as a promising noninvasive method of sampling the respiratory tract [35]. Exhaled air contains numerous VOCs, including metabolites related to both host and pathogen.…”
Section: Volatile Organic Compoundsmentioning
confidence: 99%
“…Longitudinal analysis of patients developing VA-LRTIs might shed more light on this in the near future, as it has done for the development of exacerbations in cystic fibrosis [22] and COPD [23]. A combination of analysis of the microbiome [24,25], the metabolic environment [26][27][28] and inflammatory markers [29] might provide insight into the host-pathogen interactions that are required for the development of VA-LRTIs and will provide more details on the exact immunological mechanisms that do play a role [30].…”
Section: Cough Mucociliary Clearancementioning
confidence: 99%